Career mobility in young professionals: How a protean career personality and attitude shapes international mobility and entrepreneurial intentions. Issue 1 (12th March 2018) - Baluku, Martin Mabunda; Löser, Dorothee; Otto, Kathleen; Schummer, Steffen Erik
Abstract : Purpose: The purpose of this paper is to examine the role of protean-related traits and attitudes in the development of international mobility (expatriation) and entrepreneurial intentions among early career professionals. Career mobility is of increasing relevance to achieving career success in the era of protean and boundaryless careers, and in the present day highly globalized labor market. International mobility provides opportunities for work in organizations (corporate expatriation) as well as in entrepreneurship (expat entrepreneurship). Design/methodology/approach: This paper reports two studies examining the role of "protean career personality, " conceptualized as consisting of personal initiative and flexibility on entrepreneurial and expatriation intention, looking at career orientation attitude as the mediating mechanism. In study 1, the impact of personal initiative and flexibility on the two career mobility paths is explored using a sample of 442 German undergraduate students. Study 2 replicates these relationships among a sample of 100 early career professionals who graduated with a diploma in psychology. Findings: Results indicate that for the sample of undergraduate students, flexibility and career orientation were positively related to expatriation intention. However, the mediation path was non-significant. On the other hand, personal initiative and career orientation were essential for entrepreneurial intentions, with a significant mediation path. For the early career professionals in contrast, only flexibility turned out to be resourceful for both expatriation and entrepreneurial intentions. Practical implications: Suggestions for supporting early career professionals to develop interest in working abroad or in entrepreneurship are provided. Particularly, the results indicate that protean traits affect mobility intentions differently. To strengthen intentions for expatriation work, attention should be paid enhancing the ability for staying flexible when it comes to career choices. This applies to both undergraduate students and early career professionals. However, a strong career orientation is also essential to the development of expatriation intention among current students. On the other hand, enhancing proactivity could strengthen entrepreneurial intention among undergraduate students. Originality/value: This study applies protean-related traits and attitudes; and how they work together in the development of mobility intentions among undergraduate students and early career professionals. The study reveals differential roles of these traits and attitudes among these groups, with regard to expatriation and entrepreneurship. This is important for career guidance.